Assessment of the pathogenicity of fusarium euwallaceae to grapevine and deciduous fruit trees in South Africa and its rapid detection in woody tissues - De Jager, Muriel Mignon (Stellenbosch : Stellenbosch University, 2022)
Thesis (MScConsEcol)--Stellenbosch University, 2022.